Implementing the Learning to Read: Reading to Learn Strategy for Enhancing Proficiency in Writing English Texts - Yurnalis Akbar; Santi Sardi (FITK UIN Walisongo Semarang, 2023)
This research aims to improve students' writing skills by using the Learning to read: Reading to learn strategy. This classroom action research took class XII MIA MAN 2 Tanah Datar students as objects using 2 cycles with planning, observation, reflection and revision steps. The findings of this research show that by implementing the Learning to read: Reading to learn strategy, it is able to increase students' enthusiasm and activeness in the teaching and learning process and also improve their writing skills. This can be seen from the results of observations and their writing scores which increased from pre-cycle, cycle 1 and cycle 2. The average score of student learning outcomes in the pre-cycle was 47% completeness, while in cycle 1 the result was 79.4% completeness and in cycle 2 their completion increased to 85.2%. The results of this research are effective in improving students' writing skills, and can increase students' enthusiasm and activeness in the teaching and learning process. Apart from that, the results of this research also show that the use of this method can make a positive contribution to improving the quality of learning. With an increase in the average value of student learning outcomes, this indicates that this method has the potential to be applied in other learning contexts to improve the quality of education